Safety Issues of the Russian Educational System - SIDOROVA, Ekaterina Zakarievna; VASILIEV, Alexey Mikhailovich; PELEVIN, Sergei Igorevich; TARUBAROV, Vladimir Viktorovich; OKRUZHKO, Viktoria Yurievna (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).22, 2020)
The authors of the research states that the educational system is very fragile and requires maximum protection from various threats and challenges, including those of criminal nature. Such threats comprise education workers’ crimes as well. The authors analyze qualitative and quantitative indicators of such crimes and provides the official statistics that characterize the crimes committed by teaching staff and other workers of the educational sphere. The authors pay special attention to the following corruption crimes: receiving bribes, fraud, misappropriation, and embezzlement committed by the educational sphere workers. Other types of corruption crimes in the field of education are less common; they are commercial bribery, giving bribes, mediation in bribery, legalization (laundering) of money or other property acquired by criminal means. The authors note that the official statistics indicate the formation of a trend towards a decrease in recorded crimes in the educational sector in the current period. In 2013, there were 1,344 cases of bribes received by education workers, whereas in 2017, only 329 such crimes were committed according to the official data. In this case, the rate of these crimes is decreased by minus 76%. According to the authors, such a significant reduction in indicators can be explained by various hypotheses that are presented in this study. In addition, the article states that as a result of committing criminal acts, the educational system suffers material damage in the amount of about 40 million rubles annually. At the same time, modern statistical reporting does not contain information about other types of harm to the educational environment, which does not always reflect modern realities. In conclusion, the authors states that despite all preventive measures, crimes are still committed in the educational environment, which indicates the need to develop new approaches to the issue of combating crimes committed by education workers.